Strategi Pengembangan Bisnis PT. Pintar Pemenang Asia Untuk Memperluas Jaringan Platform Pendidikan Di Indonesia Melalui Pendekatan Opportunity Seeking Dan Advantage Seeking: Suatu Kajian Pengabdian Masyarakat - Miranda Maharani; Indah Respati Kusumasari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service is carried out by the Business Development Intern division which aims to review the business development strategy of PT. Pintar Pemenang Asia in expanding the education platform network in Indonesia through an opportunity seeking and advantage seeking approach. In developing an educational platform, it is important to understand stakeholder needs, analyze market potential, develop relevant features and content, improve accessibility, and provide training and guidance to users. The results of the community service carried out by the Business Development Intern division show that PT. Pintar Pemenang Asia has an important role in providing an educational platform in Indonesia. Opportunity seeking and advantage seeking approaches help companies identify potential business opportunities and take advantage of their advantages.